Reviewing the Dental Students Skills and Habits in Kerman University of Medical Sciences Iran - Molouk Torabi; Jahangir Haghani; Jahangir Haghani; Iman Mousavi (Kerman University of Medical Sciences, 2014)
Background & Objective: Adequate time and an organized plan to study have an efficient role in improvement educational performance This study was performed to determine the dental students skills and habits in Kerman dental students   Methods: This crosssectional study was conducted on Kerman dental students in 2013 Data were collected by questionnaire in 2 parts demographic characteristics and study skill and habits consist of 24 questions in 6 domains Higher scores indicated more appropriate study skills and habits   Results: 481% were males and 519% were females with mean age of 2346 ± 609 years The mean score was 7132 ± 1065 out of 120 There was a significant correlation between the students total mean score (P = 0049) mean of study hours (P = 0033) and studying before class (P = 0050) with the mean score of questionnaire 77% 859% and 64% had good study skills moderate and poor study skills and habits respectively 519% had 24 hours daily study and 468% had 68 hours daily in exams interval   Conclusion: Study skills and habits in this study were moderate Teaching study skills can help dental students in better learning and understanding